Transmission of COVID-19 in the terminal stages of the incubation period: A familial cluster. (July 2020) - Li, Peng; Fu, Ji-Bo; Li, Ke-Feng; Liu, Jie-Nan; Wang, Hong-Ling; Liu, Lei-Jie; Chen, Yan; Zhang, Yong-Li; Liu, She-Lan; Tang, An; Tong, Zhen-Dong; Yan, Jian-Bo
Highlights: We report a familial cluster of COVID-19 to assess potential transmission of the disease during the incubation period. A familial cluster of four patients with COVID-19 in Zhoushan, China had contact with an asymptomatic family member, who developed symptoms later. The infectivity during the incubation period for SARS-CoV-2 is a big challenge for controlling the disease. Abstract: We report a familial cluster of 2019 novel coronavirus disease (COVID-19) to assess its potential transmission during the incubation period. The first patient in this familial cluster was identified during the presymptomatic period, as a close contact of a confirmed patient. Five family members had close contact with this first patient during his incubation period, with four of them confirmed positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the subsequent sampling tests.